Birth preparedness and complication readiness among women of reproductive age in Kenya and Tanzania: a community-based cross-sectional survey - James Orwa; Samwel Maina Gatimu; Michaela Mantel; Stanley Luchters; Michael A. Mugerwa; Sharon Brownie; Leonard Subi; Secilia Mrema; Lucy Nyaga; Grace Edwards; Loveluck Mwasha; Kahabi Isangula; et al. (BMC, 2020)
Abstract Background Delayed health-seeking continues to contribute to preventable maternal and neonatal deaths in low resource countries. Some of the strategies to avoid the delay include early preparation for the birth and detection of danger signs. We aimed to assess the level of practice and factors associated with birth preparedness and complication readiness (BPCR) in Kenya and Tanzania. Methods We conducted community-based multi-stage cross-sectional surveys in Kilifi and Kisii counties in Kenya and Mwanza region in Tanzania and included women who delivered two years preceding the survey (2016-2017). A woman who mentioned at least three out of five BPCR components was considered well-prepared. Bivariate and multivariable proportional odds model were used to determine the factors associated with the BPCR. The STROBE guidelines for cross-sectional studies informed the design and reporting of this study. Results Only 11.4% (59/519) and 7.6% (31/409) of women were well-prepared for birth and its complications in Kenya and Tanzania, respectively, while 39.7 and 30.6% were unprepared, respectively. Level of education (primary: adjusted odds ratio (aOR): 1.59, 95% CI: 1.14-2.20, secondary: aOR: 2.24, 95% CI: 1.39-3.59), delivery within health facility (aOR: 1.63, 95% CI: 1.15-2.29), good knowledge of danger signs during pregnancy (aOR: 1.28, 95% CI: 0.80-2.04), labour and childbirth (aOR: 1.57, 95% CI: 0.93-2.67), postpartum (aOR: 2.69, 95% CI: 1.24-5.79), and antenatal care were associated with BPCR (aOR: 1.42, 95% CI: 1.13-1.78). Conclusion Overall, most pregnant women were not prepared for birth and its complications in Kilifi, Kisii and Mwanza region. Improving level of education, creating awareness on danger signs during preconception, pregnancy, childbirth, and postpartum period, and encouraging antenatal care and skilled birth care among women and their male partners/families are recommended strategies to promote BPCR practices and contribute to improved pregnancy outcomes in women and newborns.